Population Growth and Economic Development in Developing and Developed Countries - Khairul Amri Kamarudin, Mohd; Abd Wahab, Noorjima; Mohamad, Mahadzirah; Shakir Mohd Saudi, Ahmad; Shaharudin Samsurijan, Mohamad; Hafiz Md. Saad, Muhammad; Nuratiqah Yusri, Siti; Aula Ahmad Sazali, Nurwahidatul; Fadhlina Afiqah Abdul Latif, Nur; Norsyafawati, Siti; Rahim, Abdul; Najiha Syuhada Samsuring, Nurul; et al. (International Journal of Engineering and Technology, 2018)
This research examines the effects of population growth on the economic development between the two developed and developing countries which is Singapore and Malaysia. They were many previous studies that have sought to gauge the effects or impact of population growth along the economic development. It was said that there was a strong relationship between the effects of population growth and the economic development, which is the growth of population is depending on the economic growth. Singapore was well known worldwide as a highly developed free-market economy. The economy of Singapore has been ranked as the most open in the world and the most-pro business. The population in the country is estimated at 5.5 million recently. As for Malaysia, it is known as the most competitive developing countries and is ranked on the 5th largest in South Asia. The population estimated at 31.63 million in Malaysia.Â Â